MiR‐142‐3p functions as a tumor suppressor by targeting RAC1/PAK1 pathway in breast cancer. Issue 5 (31st October 2019) - Xu, Tao; He, Bang‐Shun; Pan, Bei; Pan, Yu‐Qin; Sun, Hui‐Ling; Liu, Xiang‐Xiang; Xu, Xue‐Ni; Chen, Xiao‐Xiang; Zeng, Kai‐Xuan; Xu, Mu; Wang, Shu‐Kui
Abstract: MicroRNA‐142‐3p (miR‐142‐3p) was previously investigated in various cancers, whereas, it's role in breast cancer (BC) remains far from understood. In this study, we found that miR‐142‐3p was markedly decreased both in cell lines and BC tumor tissues. Elevated miR‐142‐3p expression suppressed growth and metastasis of BC cell lines via gain‐of‐function assay in vitro and in vivo. Mechanistically, miR‐142‐3p could regulate the ras‐related C3 botulinum toxin substrate 1 (RAC1) expression in protein level, which simultaneously suppressed the epithelial‐to‐mesenchymal transition related protein levels and the activity of PAK1 phosphorylation, respectively. In addition, rescue experiments revealed RAC1 overexpression could reverse tumor‐suppressive role of miR‐142‐3p. Our results showed miR‐142‐3p could function as a tumor suppressor via targeting RAC1/PAK1 pathway in BC, suggesting a potent therapeutic target for BC treatment. Abstract : MiR‐142‐3p is downregulated in breast cancer (BC) tissues and cell lines. MiR‐142‐3p may act as a tumor suppressor by regulating cell proliferation, migration, invasion, angiogenesis, and epithelial‐to‐mesenchymal transition process through directly downregulation of ras‐related C3 botulinum toxin substrate 1 expression and subsequently inhibiting the activity of PAK1 phosphorylation in BC.